In defence of a single body of clinical and public health, medical ethics - Jean-Pierre Unger; Ingrid Morales; Pierre De Paepe; Michel Roland (BMC, 2020)
Abstract Background Since some form of dual clinical/public health practice is desirable, this paper explains why their ethics should be combined to influence medical practice and explores a way to achieve that. Main text In our attempt to merge clinical and public health ethics, we empirically compared the individual and collective health consequences of two illustrative lists of medical and public health ethical tenets and discussed their reciprocal relevance to praxis. The studied codes share four principles, namely, 1. respect for individual/collective rights and the patient's autonomy; 2. cultural respect and treatment that upholds the patient's dignity; 3. honestly informed consent; and 4. confidentiality of information. However, they also shed light on the strengths and deficiencies of each other's tenets. Designing a combined clinical and public health code requires fleshing out three similar principles, namely, beneficence, medical and public health engagement in favour of health equality, and community and individual participation; and adopting three stand-alone principles, namely, professional excellence, non-maleficence, and scientific excellence. Finally, we suggest that eco-biopsychosocial and patient-centred care delivery and dual clinical/public health practice should become a doctor's moral obligation. We propose to call ethics based on non-maleficence, beneficence, autonomy, and justice - the values upon which, according to Pellegrino and Thomasma, the others are grounded and that physicians and ethicists use to resolve ethical dilemmas - "neo-Hippocratic". The neo- prefix is justified by the adjunct of a distributive dimension (justice) to traditional Hippocratic ethics. Conclusion Ethical codes ought to be constantly updated. The above values do not escape the rule. We have formulated them to feed discussions in health services and medical associations. Not only are these values fragmentary and in progress, but they have no universal ambition: they are applicable to the dilemmas of modern Western medicine only, not Ayurvedic or Shamanic medicine, because each professional culture has its own philosophical rationale. Efforts to combine clinical and public health ethics whilst resolving medical dilemmas can reasonably be expected to call upon the physician's professional identity because they are intellectual challenges to be associated with case management.